2 Kor 10–13: "List we łzach?" - Rakocy, Waldemar (The Biblical Annals, 2017)
The literary unity of II Cor has been the subject of discussion for over two centuries. Most attention has been paid to the last four chapters of the Letter, suggesting - at the end of the previous century - that at least in some part it is the so called "Letter in tears" which Paul sent to Corinth before II Cor. The hypothesis that enjoyed a large popularity in the first half of the 20th century was rejected by many scholars in the recent decades. The arguments that were put forward against it seem sufficient at the present stage of research to accept that it is not in keeping with the reality. Instead of the abandoned hypothesis the belief is enjoyed, especially in the Anglo-Saxon countries, that Chapters 10-13 were written some time after 1-9. Although equally important arguments against this hypothesis cannot be presented as against the previous one, this does not necessarily mean that it is true. If the literary unity of II Cor is not accepted, the solution to the problem should be looked for in the history of the Letter’s redaction. Results of this research may lead to the conclusion that a solution of the intricate problem of Chapters 10-13 is beyond our possibilities.